ANAK BERKEBUTUHAN KHUSUS: TANTANGAN DAN PELUANG DALAM PENDIDIKAN TANPA DISKRIMINASI DI TK KRISTEN TABGHA NARWASTU BATAM - Hutabarat, Johannes; Situmeang, Ameria (UPPM Sekolah Tinggi Teologi Tabgha Batam, 2025)
Children with special needs often face various challenges in proper education without discrimination, such as accessibility, curriculum adjustments, and social stigma. Education based on non-discrimination aims to provide an equal and friendly learning environment for all children, including those with special needs. In its implementation, various educational obstacles such as limited resources for students with special needs, lack of training for teaching staff, and inadequate infrastructure often hinder this process. However, education for children with special needs without discrimination also offers great opportunities, including positive social development, improving academic skills according to individual needs, and contributing to the acceptance and appreciation of diversity in society. With the right support from the government, schools, families and communities, the challenges of non-discriminatory education for children with special needs can be overcome, allowing every child to reach their maximum potential.